4x+43=6x+17

Simple and best practice solution for 4x+43=6x+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+43=6x+17 equation:



4x+43=6x+17
We move all terms to the left:
4x+43-(6x+17)=0
We get rid of parentheses
4x-6x-17+43=0
We add all the numbers together, and all the variables
-2x+26=0
We move all terms containing x to the left, all other terms to the right
-2x=-26
x=-26/-2
x=+13

See similar equations:

| 5. (x+8)2-x(x+8)=0 | | 3+5-7x=-64 | | 10=7t+9 | | 8x+7=-7+6x+18 | | 9(x+5)+7(x+5)=6x-6 | | -6(k-2)+4k=54 | | 2x(2x+3)+2x=(3x+5)= | | 5(23-10r)=15 | | 5*1.8y=9y | | 3+5(x-1)=16+3x | | 2a+2/3=8 | | 2(4−3x)=8x−13 | | 225-4x=62 | | 5(3x-4)-x=8 | | 3-(23+15n)=25 | | 20x-4=168÷x | | 0.2=14-(5.6+x) | | 2x+5(x-1)=6-3x | | 6–y=2y–6 | | .2=(14-(5.6+x) | | 2x=5(x-1)=6-3x | | x2+5x–104=0 | | 2y+8=3+5 | | 3e=3÷4 | | 7+x=0.54x-2) | | H(-2)=-x^2-5x | | 5z-14=2(-14-z) | | 7x+21=42-6+4x | | 17-3.z=5+z | | 20=1/2(8x+8+20-2x) | | -(4x-4)+5x=2x+8 | | 17-3.z=5.z |

Equations solver categories